2015
DOI: 10.4028/www.scientific.net/ddf.365.237
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Degassing and Nanoclay Loading on Physical and Flexural Properties of Epoxy

Abstract: The mechanical and physical properties of epoxy-clay nanocomposites are known to be significantly affected by the dispersion and distribution of the clay particles in the epoxy matrix. The degree of dispersion of the clay particles in the epoxy matrix depends mainly on the processing parameters used to synthesize the nanocomposite.In this paper, the optimized high shear mixing parameters determined in an earlier work were used to disperse five different loadings of Nanomer I.30E nanoclay (1, 1.5, 2, 3 and 5 wt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Cracks usually initiate in these preferred zones, which results in early or premature failure of the nanocomposites during the mechanical tests, thus suggesting the lower mechanical properties of the developed composites at 10 wt% clay loading. Ali et al also made a similar inference in their study.…”
Section: Resultssupporting
confidence: 78%
“…Cracks usually initiate in these preferred zones, which results in early or premature failure of the nanocomposites during the mechanical tests, thus suggesting the lower mechanical properties of the developed composites at 10 wt% clay loading. Ali et al also made a similar inference in their study.…”
Section: Resultssupporting
confidence: 78%
“…The selection of the right curing agent and the right quantity is a critical task as it determines the structure and properties of epoxy-clay nanocomposite [16]. Along with the curing agent, several other factors are to be considered during curing such as degassing time and temperature, as well as curing time and temperature [47,57,58]. Pre-curing time and temperature have a significant effect on crosslinking of samples [57].…”
Section: Processing Methods and Techniquesmentioning
confidence: 99%
“…However, the effect of pre-curing temperature is found to vanish when post-curing at high temperature is used [57]. With regards to degassing, some efforts [58] have shown that increasing degassing temperature and time can enhance the diffusion of epoxy into intergallery of nanoclay platelets.…”
Section: Processing Methods and Techniquesmentioning
confidence: 99%
“…Furthermore, the behaviour of the produced nanocomposites is known to be that of brittle materials [1,5,35].…”
Section: Influence Of Notch Radius On Fracture Toughnessmentioning
confidence: 99%
“…type samples of neat epoxy and epoxy-clay nanocomposites containing clay loadings of 3 (NC 3%) and 5 wt% (NC 5%) were fabricated. The nanocomposites were prepared according to the optimised curing and degassing conditions and high shear mixing technique developed in an earlier work[1,5,[33][34][35]. XRD, SEM and TEM analyses have revealed that these optimised conditions result in an epoxy/clay nanocomposite with a combination of disordered intercalated and exfoliated morphology.…”
mentioning
confidence: 99%